Effect of low level nozzle height on properties of copper oxide absorption layer prepared by fully computerized spray pyrolysis depositions - Essa, Mohammed S. (Iraqi Journal of Physics, 2019)
The effect of approaching nozzle jet from the deposition surfaceon structural, optical and morphology properties of copper oxide thinfilms was studied. The film was prepared by homemade fullycomputerized CNC spray pyrolysis deposition technique atpreparations speed (3, 4, 5, and 6 mm/sec). The repeated line modewas used at deposition temperature equal 450 °C whereas thespraying time was in the range of (15-30 min) according to thedeposition speed. The film exhibit polycrystalline structure withpreferred orientation along (-111), (022) and (011), (002) at a 2θvalue of (35.63o) and (38.8o) respectively. Optical band gaps wererecorded at these speed shows variance in value from (1.53-2.08 eV).Films thickness were found to be in the range (128-412 nm) whichdepends on preparation speed.